2016
DOI: 10.1074/mcp.m116.058800
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics-driven Antigen Discovery for Development of Vaccines Against Gonorrhea

Abstract: Expanding efforts to develop preventive gonorrhea vaccines is critical because of the dire possibility of untreatable gonococcal infections. Reverse vaccinology, which includes genome and proteome mining, has proven very successful in the discovery of vaccine candidates against many pathogenic bacteria. However, progress with this approach for a gonorrhea vaccine remains in its infancy. Accordingly, we applied a comprehensive proteomic platform-isobaric tagging for absolute quantification coupled with two-dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
178
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(198 citation statements)
references
References 102 publications
(144 reference statements)
13
178
0
Order By: Relevance
“…1D). In our proteomic profiling, we found that this protein was upregulated during growth under iron-limited conditions (5). The meningococcal homolog, NMB1971, has been described as a paralog of the surface lipoprotein assembly modulator Slam and was designated Slam2.…”
mentioning
confidence: 92%
See 3 more Smart Citations
“…1D). In our proteomic profiling, we found that this protein was upregulated during growth under iron-limited conditions (5). The meningococcal homolog, NMB1971, has been described as a paralog of the surface lipoprotein assembly modulator Slam and was designated Slam2.…”
mentioning
confidence: 92%
“…1C). We have recently determined that NGO2054 is surface exposed, induces bactericidal antibodies, and is continuously expressed at the same level throughout all stages of gonococcal growth and under tested host-relevant conditions (5).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The estradiol-treated female mouse model [16] has now been applied to this effort [17], and further refinements of the model using transgenic mice that express various human factors involved in gonococcal pathogenesis afford scope for more detailed analysis of the mechanisms whereby immune protection can be attained [10]. Third, efforts are now underway to apply proteomics technology to the discovery of novel, conserved surface antigens shared by different strains of N. gonorrhoeae [18]. Already some initial candidate antigens have been identified, although these have not yet been evaluated in animal models of protection.…”
Section: Editorial Russellmentioning
confidence: 99%